2023
DOI: 10.1002/hon.3171
|View full text |Cite
|
Sign up to set email alerts
|

[18F]‐FDG PET radiomic model as prognostic biomarker in diffuse large B‐cell lymphoma

Abstract: To evaluate the association between radiomic features (RFs) extracted from 18F‐FDG PET/CT (18F‐FDG‐PET) with progression‐free survival (PFS) and overall survival (OS) in diffuse large‐B‐cell lymphoma (DLBCL) patients eligible to first‐line chemotherapy. DLBCL patients who underwent 18F‐FDG‐PET prior to first‐line chemotherapy were retrospectively analyzed. RFs were extracted from the lesion showing the highest uptake. A radiomic score to predict PFS and OS was obtained by multivariable Elastic Net Cox model. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Additionally, ROC curves indicated that Rad-score predicted AUC and accuracy values of 3 and 5-year OS in the validation cohorts were 0.787 and 69.5%, respectively, 0.563 and 63.6%, respectively, with a signi cantly reduced AUC value for the latter. Travaini et al also reported that the Rad-score basing the baseline 18F-FDG-PET was an independent prognostic biomarker of survival in DLBCL patients, and the C-index of OS was 0.84 [24] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, ROC curves indicated that Rad-score predicted AUC and accuracy values of 3 and 5-year OS in the validation cohorts were 0.787 and 69.5%, respectively, 0.563 and 63.6%, respectively, with a signi cantly reduced AUC value for the latter. Travaini et al also reported that the Rad-score basing the baseline 18F-FDG-PET was an independent prognostic biomarker of survival in DLBCL patients, and the C-index of OS was 0.84 [24] .…”
Section: Discussionmentioning
confidence: 95%
“…Zhao et al [30] reported an accuracy of 76.3% in predicting 2-year OS of DLBCL patients based on a combined FDG-PET/CT clinical-radiomic model, and the prediction accuracy of the nomogram model in this study is close to theirs. Travaini et al [24] reported that a combined clinicalradiomic model based on FDG-PET/CT predicted that the C-index of OS in DLBCL patients with rst-line chemotherapy was 0.90. The accuracy of the nomogram model in this study is still a certain distance from theirs.…”
Section: Discussionmentioning
confidence: 99%